MENATA PENGEMBANGAN KARIER SUMBER DAYA MANUSIA ORGANISASI - Mohamad Muspawi (Jurnal Ilmiah Universitas Batanghari Jambi, 2017)
Career development is a demand and the needs of both the employer / employee and for the organization. For employee career development is the way to grow and achieve successes in work, whereas for the organization of career development is an attempt to bring the employee / employees who are professional and have experience of working stages.Career development is the effort made by the organization in planning for a career employees, referred to as career management, including planning, implementing, and overseeing the careers (Sinambela, 2016: 260). Career development is a series of activities to prepare an individual on a planned career advancement (Mondy, 1993).Samsudin (2010: 151-152) explains that the development of a career as a human resources management activities is the realization of the individual as a worker relationship with the organization. To realize the career self-management, the necessary conditions: a. Awareness and understanding of the work that every job always provides an opportunity to grow and progress. b. Each worker must understand the responsibility for career development is an individual responsibility that each individual should perform self-management career. c. Each worker is always aware and understand that it is not easy for society together to provide a form of career positions available.Keywords:  Career development, human resources.